Art 21 art in the 21st century. Seasons four (Art21, Inc. ;distributed by PBS Home Video, 2007)
Visually captivating and intriguing, contemporary art is admired and appreciated by many in museums and galleries. Yet few are given access to the creative processes behind the work--the inspirations and ideas that translate into compelling finished objects. This fall, "Art:21 will provide the Twenty-First Century" returns to PBS for its forth season. Through in-depth profiles and interviews, the four-part series will reveal the inspiration, vision and techniques behind the creative works of some of today's most accomplished contemporary artists. [from pbs.org].